Investigação ação escolar: situação-problema na aprendizagem de conceitos matemáticos - Pereira, Vera Lúcia Biscaglia (2008)
In this research it was followed the conception that situation-problem is a main point to start learning mathematical concepts, as suggested by PCN, and not a mere acquired content s application. It was actively investigated, aiming at an approximation of practical and school knowledge in order to improve learning through situation-problems. The methodological proceedings used were based on a qualitative approach, through an investigation-action cycle in the problematizing-dialogic perspective, in which the school practices were carried out to answer the following question: analyzing practical and school knowledge, through situation-problems, contributes to the learning of mathematical concepts? During the situation-problems solution, the students acted in the context they live, simulating, weighing and measuring lengths, becoming more active and motivated due to these proceedings. Through dialogues, they have expressed the new relation they were doing with what they have learned day by day during the situation-problems solving. The students noticed themselves differently facing the lived experiences because they have observed information around them and related to what was studied in class. From these declarations, it was possible to notice that there is possibility in relating practical and school knowledge through situation-problems in the mathematical school practices. Considering that teaching through situation-problems emphasizes interaction among mathematical concepts, action, observation and analyzes, minimizing operatory process of mechanical form, can develop a more integrated theoretical and practical knowledge, and turn school practices more motivating and dynamic.